Inhibition of synaptic transmission by anandamide precursor 20:4-NAPE is mediated by TRPV1 receptors under inflammatory conditions - Spicarova, Diana; Nerandzic, Vladimir; Muzik, David; Pontearso, Monica; Bhattacharyya, Anirban; Nagy, Istvan; Palecek, Jiri (Frontiers in Molecular Neuroscience, 2023)
Transient receptor potential ion channel, vanilloid subfamily, type 1 (TRPV1) cation channel, and cannabinoid receptor 1 (CB1) are essential in the modulation of nociceptive signaling in the spinal cord dorsal horn that underlies different pathological pain states. TRPV1 and CB1 receptors share the endogenous agonist anandamide (AEA), produced from N-arachidonoylphosphatidylethanolamine (20:4-NAPE). We investigated the effect of the anandamide precursor 20:4-NAPE on synaptic activity in naive and inflammatory conditions. Patch-clamp recordings of miniature excitatory postsynaptic currents (mEPSCs) from superficial dorsal horn neurons in rat acute spinal cord slices were used. Peripheral inflammation was induced by subcutaneous injection of carrageenan. Under naive conditions, mEPSCs frequency (0.96 ± 0.11 Hz) was significantly decreased after 20 μM 20:4-NAPE application (55.3 ± 7.4%). This 20:4-NAPE-induced inhibition was blocked by anandamide-synthesizing enzyme N-acyl phosphatidylethanolamine phospholipase D (NAPE-PLD) inhibitor LEI-401. In addition, the inhibition was prevented by the CB1 receptor antagonist PF 514273 (0.2 μM) but not by the TRPV1 receptor antagonist SB 366791 (10 μM). Under inflammatory conditions, 20:4-NAPE (20 μM) also exhibited a significant inhibitory effect (74.5 ± 8.9%) on the mEPSCs frequency that was prevented by the TRPV1 receptor antagonist SB 366791 but not by PF 514273 application. Our results show that 20:4-NAPE application has a significant modulatory effect on spinal cord nociceptive signaling that is mediated by both TRPV1 and CB1 presynaptic receptors, whereas peripheral inflammation changes the underlying mechanism. The switch between TRPV1 and CB1 receptor activation by the AEA precursor 20:4-NAPE during inflammation may play an important role in nociceptive processing, hence the development of pathological pain.